Factors Influencing Decreased Wheat Crop Yield in 2021-22 - Shamsur Rehman; Zaryab Shah; Maleeha Mehboob; Raja Zohaib Muqarrab; Sami Ullah kakar (MultiTech Publisher, 2022)
Wheat is one of the most important sources of cereal grain which fulfills the food needs of around 40% of the world population. Numerous factors are responsible for the low yield of wheat like abiotic factors and low yielding varieties, improper inputs such as irrigation and fertilizers, sowing time, weeds, insect pests, post-harvest loses, temperature and moisture. A vast survey was conducted at University of Agriculture Peshawar Khyber Pakhtunkhwa to know about the grain yield losses of wheat from 2021 to 2022 This survey is based on grain yield losses of wheat by various factors. According to survey the highest spike m-2 losses (314) was occurred in 2020 followed by 2022, the highest grains spike-1 losses (16) and lighter thousand grain weight (41.21 g) was recorded in 2022 year while total grain yield the more grain yield losses was occured in 2021.Wheat cultivation decreased to 8,976 thousand hectares (2.1 %) against last years of 9,168 thousand hectares. The production of wheat declined to (3.9 %) compared to last year. In wheat the highest yield losses was occurred at tiller loss 39.8% by underground pest followed by lodging at reproductive stage 38% while lowest yield loss was recorded at grain spike-1 at field by birds eating which is 15.1%. The average loss of yield occured in wheat is 24.1%. It is concluded that various factors, including abiotic influences, improper inputs, pests, and post-harvest issues, contribute to wheat yield losses, highlighting the need for targeted interventions to enhance wheat production and mitigate these losses